Study of Angiogenesis-Related Phosphodiesterase Inhibitors - Renato Paladino Nemoto, Barbara Pavin, Bruna Abreu Canteras, Alexia Hallack Dreicon, Gustavo Ramalho Fernandes, Giuliana Petri, Fernando Luiz Afonso Fonseca , David Feder (Journal of Applied Pharmaceutical Science, 2015)
Angiogenesis is the process through which new capillaries form from pre-existing capillaries and venules. Its occurrence depends on the migration of vascular endothelial cells which is inhibited by high levels of cAMP. Such levels can be regulated by the degradation caused by the phosphodiesterases (PDEs). Therefore, by inhibiting the action of PDEs it is assumed that angiogenesis can be inhibited with the prevention of migration of these cells. The aim of this study was to evaluate the effect PDE inhibitors on angiogenesis in mice by using non-specific inhibitors (aminophylline) and selective inhibitors of PDE4 (roflumilast) and PDE5 (sildenafil). BALB/c mice were used as a model; under anesthesia, the mice had a sponge of 0.5 x 0.5 cm introduced into their dorsal subcutaneous tissue; they were then divided into 4 groups and daily gavage treated: 1) control group (n=13) – treated with 0.3 mL of saline solution; 2) aminophylline group (n=16) – 50 mg/kg; 3) roflumilast group (n=14) – 5mg/kg; 3) sildenafil group (n=12) –100 mg/kg. After 7 days, with the animals anesthetized, a blood sample was drawn for hemoglobin (Hb) measurement, the sponge implant was removed, and its content was obtained in 2 mL of saline solution for hemoglobin measurement. Absorbance levels (A), the amount of Hb from the sponge (S) and the total blood Hb concentration levels from each mouse were evaluated. According to the results obtained, we concluded that aminophylline, roflumilast and sildenafil (phosphodiesterase inhibitors) did not cause any alteration in the angiogenesis evaluated by the sponge-implantation method.
Keywords: Angiogenesis,Angiogenesis Inhibitors,Cyclic Nucleotide Phosphodiesterase, Phosphodiesterase Inhibitors.